Limites e possibilidades da Economia Solidária: um projeto de realismo utópico - Gomes, Edgar da Nóbrega (2011)
In a time of crisis, of biases and paradoxes, there are strong evidences regarding the inadequacies of the hegemonic development model. At the same time, there is no global evidence that an alternative way is possible. Worldwide changes with complex relations affect business, families and governments. Economic, political, social, environmental issues until recently, were analyzed based on indicators that were efficient before but no longer make sense. In this uncertain time, plenty of questions are made, but there are no answers strong enough to move "hearts and minds . Is it possible to construct other forms of organization of society? Can solidarity be considered a fundamental element of economic ideas? The construction of a theory that helps steer a new path for humanity will be the result of new values and new assumptions. Therefore, we must overcome the differences that are, sometimes, more "appearance that essence". Considering the limits and possibilities of practical experience and theoretical analysis of Solidarity Economy, there is elements that reaffirm this as an alternative utopian realism. The conclusion of this study was that there are two important issues for an agenda that considers solidarity an essential paradigm for a new economy: freedom and participation. These are central elements, the result of of conscious choices that individuals make and use these results participating rightly and wrongly, without fear of moving forward or back. It is the model of cooperative or voluntary work, solidarity economy, where people can fully exercise their freedom. Participation becomes increasingly a necessity of development processes